Mauritius : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that the Mauritian economy has weathered the global economic slowdown relatively well. Economic output is expected to expand by about 5.3 percent in 2001/02 (July-June), only slightly below its trend rate of growth of the past 20 years. Tourism weakened somewhat in the second quarter of 2001 but picked up in the second half, partly reflecting Mauritius' reputation as a safe destination. Notwithstanding the relatively robust economic growth over the past decade, unemployment has risen steadily and is projected to reach about 9 percent in 2001/02.